1984
DOI: 10.1007/bf01935811
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of methodology for measurement of intramyocardial pressure

Abstract: We critically evaluated the major techniques for measurement of intramyocardial pressure (IMP) (closed, perfusion, open, microtransducer). Each technique demonstrates a gradient in systolic IMP increasing with depth from the epicardium. The estimated magnitude of this gradient varies with the technique employed. Indirect methods (closed, perfusion) estimate a higher value for the systolic IMP gradient. The open and microtransducer methods, which measure a direct hydrostatic pressure within the myocardium, are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…In general, great care has to be taken to avoid direct contact of the sensor with the muscle and a covered or recessed transducer is used; this was recently discussed by Rabbany et al (58). It was also shown that transducer orientation may be important (54). This method was used first by Armour and Randall (6) and later by others (30,31,54,65,66).…”
Section: Microtransducer Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…In general, great care has to be taken to avoid direct contact of the sensor with the muscle and a covered or recessed transducer is used; this was recently discussed by Rabbany et al (58). It was also shown that transducer orientation may be important (54). This method was used first by Armour and Randall (6) and later by others (30,31,54,65,66).…”
Section: Microtransducer Methodsmentioning
confidence: 95%
“…This method is often called the "closed method" (54,58). An artificial cavity is created in the myocardium and pressure is measured in it.…”
Section: Isovolumic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The size and location of infarction after coronary occlusion will generally depend upon regional oxygen demands, regional oxygen and other substrate supplies, and the size and location of the tissue bed perfused by the vessel at jeopardy. In ventricular free walls, intramural systolic tension is greater in inner than in outer wall segments (14,21); indeed, subendocardial wall tension may exceed intracavitary pressure (14,21). This pressure gradient translates into a greater oxygen demand in subendocardial than in subepicardial tissues.…”
Section: Artery a F T E R Verifying T H E S E Variables An A T T E mentioning
confidence: 97%
“…This pressure was named "tissue pressure" or "intramyocardial pressure" [2]. The accuracy of its measurement depends on the size of the transducers inserted inside the left ventricular wall, large transducers providing pressure values higher than the real ones [3]. The servo-nulling method seems the solution for this problem, because it uses as sensors glass micropipettes, which are 1000 smaller than transducers used by any other method [4].…”
Section: Introductionmentioning
confidence: 99%